Epidemiology of meticillin-resistant Staphylococcus aureus bloodstream infections in Alberta, Canada. Issue 2 (February 2015) - Taylor, G.; Bush, K.; Leal, J.; Henderson, E.; Chui, L.; Louie, M.
Summary Most studies of meticillin-resistant Staphylococcus aureus (MRSA) bloodstream infection (BSI) reflect a convenience sample from a single hospital or a small group of hospitals. From April 2011 to March 2013, cases of MRSA BSI diagnosed in all hospitals in Alberta, Canada were captured prospectively. Isolates were spa typed. In total, there were 299 cases of MRSA BSI, equating to 3.95 cases per 100, 000 population. Community-acquired BSI accounted for 66.9% of cases, and 33.1% of cases were hospital acquired. Cases were predominantly seen in tertiary care (36.4%) and large urban hospitals (34.3%), but were also common in regional and rural hospitals. Paediatric hospitals had very few cases (3.0%). Two clones, CMRSA 10 (USA 300; 40.2%) and CMRSA 2 (USA 100/800; 38.0%), predominated.